PERAN PERCEIVED RISK, E-WOM, DAN BRAND IMAGE DALAM MEMBANGUN E-TRUST DAN PURCHASE INTENTION PADA APLIKASI BUKU DIGITAL - Zakiya, Hani Fildzah; Suhud, Usep; Berutu, Meta Bara (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This study aims to analyze the effect of perceived risk, e-WOM, and brand image on e-trust and purchase intention in prospective Gramedia Digital consumers. The research method used is quantitative causality. The research sample used purposive sampling technique consisting of 250 respondents who live in DKI Jakarta. The data collection technique used was a questionnaire. The data was processed using SPSS and AMOS software. The analysis technique used is Structural Equation Modeling (SEM). The results showed that perceived risk has no negative effect on e-trust and purchase intention. Meanwhile, e-WOM and brand image have a positive effect on e-trust. On the other hand, e-WOM, brand image, and e-trust have a positive effect on purchase intention. This study provides theoretical implications by supporting previous research in the context of digital platforms. The practical implication for digital book companies is to focus on providing a positive user experience so that they can share positive experiences with potential buyers and build brand characteristics to compete with their competitors.